An Efficient and Scalable Synthesis of Lifitegrast. Issue 11 (17th March 2020) - Rao Yerrabelly, Jayaprakash; Kommera, Rajashekar; Reddy Kasireddy, Venkateshwer; Reddy Ghojala, Venkat; Yerrabelly, Hemasri
Abstract: An efficient and improved synthesis of a novel anti‐inflammatory drug, Lifitegrast 1 is described from Benzofuran‐6‐carboxylicacid. This synthetic approach avoided the racemization, formation of dimer impurities and furnished higher overall yield (79 %) with high purity. The key step of the synthesis involves tertiary butylester protection of the aminoacid fragment, which was hydrolyzed in further stages under mild acidic conditions. The critical process parameters were thoroughly studied for protection and deprotection of the tertiary butyl functional group. The attractive features of synthesis are the usage of commercially cheaper and eco‐friendly reagents suitable for multi kilo scale synthesis of Lifitegrast 1 . Abstract : A simple, efficient and commercially scalable approach has been developed to a new anti‐inflammatory drug, Lifitegrast. This synthetic approach avoided the racemization, formation of dimer impurities and furnished higher overall yield (79 %) with high purity. The key step of the synthesis involves tertiary butyl ester protection of the amino acid fragment, which was hydrolyzed in further stages under mild acidic conditions.